Al-Qur'an Literacy Solution for students: Assistance with the Introduction of Hijaiyah Letters Based On the Tilawati Method at NU Palangka Raya Middle School - Rahman, Zaini; Hakim, M. Luqman; Yuliani, Hadma (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service aimed to address the low proficiency in Qur'anic reading among students at NU Palangka Raya Middle School, particularly their inability to recognize and pronounce hijaiyah letters correctly. The study focused on improving Al-Qur'an literacy by facilitating effective learning of the hijaiyah alphabet using the Tilawati method, which is essential for proper tajwid application. Method: A Participatory Action Research (PAR) approach was employed, involving five stages: problem identification, joint planning, implementation, evaluation, and follow-up. The intervention targeted Class IX students during PAI (Islamic Religious Education) lessons and utilized the Tilawati method with the "rost" tone to teach hijaiyah letters through rhythmic and engaging recitation techniques. Practical Applications: The program significantly increased student enthusiasm and participation, leading to improved recognition and pronunciation of hijaiyah letters. Teachers observed enhanced engagement and retention, indicating that the Tilawati method can be effectively integrated into regular classroom instruction to make Qur'anic learning more enjoyable and accessible. Conclusion: The implementation of the Tilawati method through a collaborative PAR framework successfully improved students’ foundational Qur'anic reading skills. This approach not only strengthened religious education but also provided a replicable model for enhancing Al-Qur'an literacy in similar educational contexts.